Assessing the statewide impact of the Specter Vocational Program on reentry outcomes: A propensity score matching analysis. Issue 1 (2nd January 2017) - Hill, Leslie; Scaggs, Samuel J. A.; Bales, William D.
ABSTRACT: The Specter program was a vocational work program offered by the Florida Department of Corrections from 1997–2012. Using propensity score matching, inmates who earned a Specter vocational certificate had statistically significantly lower rates of recidivism within three years of release from prison compared to inmates who had not earned a certificate. However, those who earned a Specter certificate did not have statistically significant improvements in postrelease employment within three months of release. As a result, we will discuss the possibilities for conflicting findings regarding employment and recidivism as well as potential avenues for future research.